Comment exploiter la forêt sans la détruire ? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Un atelier de travail sur l'aménagement et la conservation de l'écosystème forestier tropical humide s'est tenu